Chinese Herbal Medicine for Primary Liver Cancer Therapy: Perspectives and Challenges - Li, Kexin; Xiao, Kunmin; Zhu, Shijie; Wang, Yong; Wang, Wei (Frontiers in Pharmacology, 2022)
Primary liver cancer (PLC) is one of the most common solid malignancies. However, PLC drug development has been slow, and first-line treatments are still needed; thus, studies exploring and developing alternative strategies for effective PLC treatment are urgently needed. Chinese herbal medicine (CHM) has long been applied in the clinic due to its advantages of low toxicity and targeting of multiple factors and pathways, and it has great potential for the development of novel natural drugs against PLC. Purpose: This review aims to provide an update on the pharmacological mechanisms of Chinese patent medicines (CPMs) and the latest CHM-derived compounds for the treatment of PLC and relevant clinical evaluations. Materials and Methods: A systematic search of English literature databases, Chinese literature, the Clinical Trials Registry Platform, and the Chinese Clinical Trial Registry for studies of CHMs for PLC treatment was performed. Results: In this review, we summarize the clinical trials and mechanisms of CPMs for PLC treatment that have entered the clinic with the approval of the Chinese medicine regulatory authority. These CPMs included Huaier granules, Ganfule granules, Fufang Banmao capsules, Jinlong capsules, Brucea javanica oil emulsions, and compound kushen injections. We also summarize the latest in vivo, in vitro, and clinical studies of CHM-derived compounds against PLC: icaritin and ginsenoside Rg3. Dilemmas facing the development of CHMs, such as drug toxicity and low oral availability, and future developments are also discussed. Conclusion: This review provides a deeper the understanding of CHMs as PLC treatments and provides ideas for the development of new natural drugs against PLC.